2019
DOI: 10.1038/s41598-019-46076-0
|View full text |Cite
|
Sign up to set email alerts
|

Postbiotic L. plantarum RG14 improves ruminal epithelium growth, immune status and upregulates the intestinal barrier function in post-weaning lambs

Abstract: We investigate the effects of postbiotic Lactobacillus plantarum RG14 on gastrointestinal histology, haematology, mucosal IgA concentration, microbial population and mRNA expression related to intestinal mucosal immunity and barrier function. Twelve newly weaned lambs were randomly allocated to two treatment groups; the control group without postbiotic supplementation and postbiotic group with supplementation of 0.9% postbiotic in the diet over a 60-day trial. The improvement of rumen pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 67 publications
3
47
0
1
Order By: Relevance
“…Supplementation of lambs with probiotic B. licheniformis enhanced antioxidant capacity by elevating the SOD and GPX enzymes, as well as promoted immune function, which beneficially facilitates ruminal fermentation and microbial diversity [20]. This was also proven in our previous studies that postbiotics inclusion in the post-weaning Dorper lambs enhanced immune status and gut health and led to better nutrient utilization and growth performance [11,12].…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Supplementation of lambs with probiotic B. licheniformis enhanced antioxidant capacity by elevating the SOD and GPX enzymes, as well as promoted immune function, which beneficially facilitates ruminal fermentation and microbial diversity [20]. This was also proven in our previous studies that postbiotics inclusion in the post-weaning Dorper lambs enhanced immune status and gut health and led to better nutrient utilization and growth performance [11,12].…”
Section: Introductionmentioning
confidence: 62%
“…Upregulation of tight junction protein genes was observed in the rumen of post-weaning lambs receiving dietary postbiotic. Postbiotic supplementation in the diet of post-weaning lambs was reported to improve the intestinal barrier function simultaneously with improvement in intestinal morphology, microbial population and mucosal immunity [11]. Studies on L. plantarum as feed additives in another species showed improvement of gut barrier function accompanied by a better gut environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been observed that the dietary supplementation of postbiotics promoted the health and growth performance in broilers [31][32][33], layers [34,35] and piglets [36,37]. More recently, postbiotics have been reported enhancing the growth performance, rumen fermentation, immune status, antioxidant defence system, and gut health in small ruminants [38][39][40]. Under normal environmental temperature, dietary supplementation of postbiotics improved health and growth performance of broilers by promoting their immune status, growth genes expression and gut health as their supplementation significantly improved the intestinal villus, decreased the population of Enterobacteriaceae and faecal pH, and increased the population of lactic acid bacteria [25,[31][32][33]41].…”
Section: Introductionmentioning
confidence: 99%